How need- and norm-based motives for digital communication mitigate the chilling effects of dataveillance - Daoust-Braun, Sarah; Festic, Noemi; Latzer, Michael (AoIR Selected Papers of Internet Research, 2026)
Perceiving dataveillance, the pervasive collection and analysis of digital traces, as salient can increase internet users’ sense of dataveillance and expectations of negative consequences from digital communication, leading to self-inhibited online use. This process, known as chilling effects of dataveillance, can limit participation in today’s digital society, where being online is a need and norm. Given these potential consequences, the conditions under which chilling effects hold require empirical attention. This study investigates whether need- and norm-based motives for digital communication mitigate chilling effects, i.e., the negative effects of a heightened sense of dataveillance on digital communication. Drawing on uses and gratifications (U&G) and social norms research, we argue that users are motivated to engage in digital communication based on felt needs and perceived norms, reducing their susceptibility to chilling effects. Using survey data from a representative sample of Swiss-German internet users ( $2 = 898), we conducted mediation and moderation analyses. Supporting the core chilling effects hypothesis, preliminary results revealed that higher perceived salience of dataveillance (driving one’s sense of dataveillance) and expected consequences from digital communication were significantly associated with self-inhibition in response to a sense of dataveillance. Contrary to expectations, need- and norm-based motives did not mitigate these relationships, suggesting the robustness of chilling effects. This novel work advances our limited understanding of chilling effects’ boundary conditions by integrating U&G and social norms approaches into chilling effects and user-centered dataveillance research. It provides representative evidence aligning with theoretical mechanisms of chilling effects.